A combination of invasive and non-invasive techniques for the study of the palette and painting structure of a copy of Raphael's Transfiguration of Christ - Eloísa Manzano (SpringerOpen, 2021)
Abstract The main objective of this study is to establish an appropriate method for the characterization of the pigments, materials and structure of the paint layers in a copy of the painting the Transfiguration of Christ by Raffaello Sanzio. A multi-technique approach that combines elemental, molecular and structural analyses and involves optical microscopy (OM), scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM–EDX), μ-Attenuated Total Reflection–Fourier Transform InfraRed (µATR-FTIR), μ-Raman spectrometry (µRS) and non-invasive portable diffractometer (pXRD) was used. Our results revealed that this copy of the Transfiguration was executed with a palette, which includes white lead (cerussite and hydrocerussite), lazurite from lapis lazuli pigment, red and yellow earths (goethite, hematite and lepidocrocite), lead tin yellow, cinnabar, red lake, smalt and bone black, and fillers such as calcite, baryte (an impurity associated to some pigments), and traces of colorless powdered glass. A secondary objective of this research was the application of non-invasive in situ pXRD measurements, which do not require painting sampling and helped to confirm some inconclusive results obtained with other techniques regarding the artist's palette. The results showed the crystalline nature of all the pigments identified, which were known from ancient times and available during the 16th and 17th. Lastly, the used of 14C accelerator mass spectrometry determined that the canvas date was 1451–1633 AD (with a 95% confidence level). Although the main focus of the work was to improve the analytical methodology to better understand the artist’s palette, our results will further help us to explore the authorship of the copy or the school that executed it. Graphical Abstract